Clinical images: Osseous and subcutaneous tophus (2001)
The therapeutic effect of tumor necrosis factor (TNF)inhibition is certainly well recognized from studies usinganti-TNF monoclonal antibodies and soluble TNF receptorfusion proteins. The article by Maini et al (Maini RN, Breed-veld FC, Kalden JR, Smolen JS, Davis D, Macfarlane JD, et al.Therapeutic efficacy of multiple intravenous infusions of anti-tumor necrosis factoramonoclonal antibody combined withlow-dose weekly methotrexate in rheumatoid arthritis. Arthri-tis Rheum 1998;41:1552–63.) provides further evidence thatTNF inhibition improves signs and symptoms of rheumatoidarthritis (RA). Unfortunately, some of the statements made inthe article are either invalid or not supportable.